Remarks to the Annual Meetings 2020 Development Committee - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank Group, announced that the Board approved a fast track approach to emergency health support programs that now covers 111 countries. Most projects are well advanced, with average disbursement upward of 40 percent. The goal is to take broad, fast action early. The operational framework presented back in June has positioned the Bank to help countries address immediate health threats and social and economic impacts and maintain our focus on long-term development. The Bank is making good progress toward the 15-month target of 160 billion dollars in surge financing. Much of it is for the poorest countries and will take the form of grants or low-rate, long-maturity loans. IFC, through the Global Health Platform, will be providing financing to vaccine manufacturers to foster expanded production of COVID-19 vaccines in both part 1 and 2 countries, providing production is reserved for emerging markets. The Development Committee holds a unique place in the international architecture. It is the only global forum in which the Governments of developed countries and the Governments of developing countries, creditor countries and borrower countries, come together to discuss development and the ‘net transfer of resources to developing countries.’ The current International Financial Architecture system is skewed in favor of the rich and creditor countries. It is important that all voices are heard, so Malpass urged the Ministers of developing countries to use their voice and speak their minds today. Malpass urged consideration of how we can build a new approach to debt restructuring that allows for a fair relationship and balance between creditors and debtors. This will be critical in restoring growth in developing countries; and helping reverse the inequality.